Contributions à la connaissance de la dynamique des phosphates et des silicates des eaux marines du littoral roumain de la Mer Noire - Cociașu, Adriana; Popa, Lucia (Cercetări Marine - Recherches Marines, 2026)
This work points out certain characteristics of the distribution of the dissolved states of phosphorus and mineral silicium, determined by the hydrological and hydrobiological conditions specific to the years 1976 and 1977.